PERLAKUAN AKUNTANSI SELISIH KURS - Wibisono, Haris (Widya Warta, 2011)
This literature study aims (1) to evaluate the accounting treatments of exchange differences on Indonesia GAAP and (2) to determine the extent to which its use is beneficial for the company to present more accurate and transparent statements. The study focuses on the accounting treatments of exchange differences in financial accounting at the extraordinary depreciation. This issue is raised because of the pros and cons regarding the accounting treatments of exchange differences capitalized in SAK, especially ISAK 4. Capitalization of foreign exchange differences according to the ISAK 4 can be implemented with the conditions of extraordinary depreciation and hedging improbability. Foreign exchange differences which can be capitalized are the foreign exchange differences on foreign currency liabilities both realized or unrealized. Such obligations arise from the acquisition of property paid in foreign currency. With the maximum limit, the lower level is chosen between replacement cost and recoverable amount.